Some reflections on the history of administrative-territorial division in Central Asia - Otabek Normatov; Shohsanam Sulaymanova; Zilola Khaydarova (The Bioscan, 2024)
This article, based on various historical sources, highlights changes in the administrative-territorial division of Uzbekistan on the eve of regionalization in Central Asia, the general situation and processes. In particular, it says that national-territorial delimitation will be carried out in the republics of Central Asia, the formation of the Uzbek SSR, the zoning policy in Uzbekistan will enter a new stage, and the Soviet authorities will seriously prepare for the implementation of the zoning policy in Central Asia.